Oral Diseases in Pregnant Women and Low Birth Weight Risk: A Case-Control Study in Mantikulore Sub-District, Palu City, 2025 - Sunarsih Sunarsih; Rajindra Rajindra; Munawir Hi. Usman; Gusman Gusman (PT. Anagata Sembagi Education, 2026)
Low Birth Weight (LBW), defined as birth weight less than 2,500 grams, remains a significant public health problem in Indonesia, including Palu City. Oral diseases during pregnancy are proposed as contributing risk factors. This study aimed to analyze the relationship between oral diseases in pregnant women, dental caries, gingivitis, periodontitis, and stomatitis, with LBW incidence in Mantikulore Sub-District, Palu City, 2025. An observational analytic design with a case-control approach was employed. A total of 114 respondents were recruited (57 cases: mothers delivering LBW infants; 57 controls: mothers delivering normal-weight infants). Oral health examinations were conducted using the DMF-T index (caries), OHI-S index (oral hygiene/gingivitis), and CPITN index (periodontal status); stomatitis history was assessed via questionnaire. Data were analyzed using Chi-Square tests and multiple logistic regression. Results demonstrated significant associations: high DMF-T with LBW (OR=4.14; p=0.001), poor OHI-S with LBW (OR=9.06; p=0.000), severe CPITN with LBW (OR=6.57; p=0.000), and stomatitis with LBW (OR=24.06; p=0.000). Multivariate analysis identified stomatitis as the most dominant factor associated with LBW (OR=20.19; p=0.000), followed by poor OHI-S (OR=6.94; p=0.016). The model explained 67.5% of LBW variation. Oral health of pregnant women is significantly associated with LBW; oral health screening should be integrated into routine antenatal care.